Behavior of chemical variables of a soil subject to different uses, department of Nariño, Colombia - Arteaga J., Julio César; Navia E., Jorge Fernando; Castillo, Jesús Antonio (Revista de Ciencias Agrícolas, 2016)
The present study was carries out in an Andisol of the subgrup Vitric haplustands, located in the Corregimiento of Obonuco, Municipality of Pasto (Colombia). Some chemical characteristics were evaluated, in seven different soil uses and management: T1: potato monocrop (Solanum tubersum L.), T2: Kikuyo (Pennisetum clandestinum), T3: windbreak, T4: agroforestry system acacia - aliso, T5: protein blocks, T6: forest plantation (Eucaliptus globulus Labill) and T7: native forest. The effect of the soil uses and management over the chemical properties of the soils were evaluated with the variables: pH% MO,% CO, total N, P, CIC, Ca, Mg, K, Al, Fe, Mn Cu, Zn, B and S. The data was analyzing using ANAVA, LSD and correlations of Pearson. The results showed significant differences (P <0,05) in pH contents,% MO,% CO, total N, P, CIC Ca, Mg, K, Fe and S. The higher contains of MO, CO, N, CIC, Ca, Mg and S, were obtained in the treatments T3, T4 and T7. These results allowed us to confirm the influence of MO in the fertility of soils, being MO the variable that better detects the effect of the soil use and management.